Abatement of the antibiotic levofloxacin in a solar photoelectro-Fenton flow plant: Modeling the dissolved organic carbon concentration-time relationship. (May 2018) - Coria, Gabriela; Pérez, Tzayam; Sirés, Ignasi; Brillas, Enric; Nava, José L.
Abstract: The degradation of solutions of the antibiotic levofloxacin (LVN) in sulfate medium at pH 3.0 has been investigated at pre-pilot scale by solar photoelectro-Fenton (SPEF) process. The flow plant included an FM01-LC filter-press cell equipped with a Ti|Pt anode and a three-dimensional-like air-diffusion cathode, connected to a compound parabolic collector as photoreactor and a continuous stirred tank under recirculation batch mode. The effect of volumetric flow rate on H2 O2 electrogeneration from O2 reduction was assessed. Then, the influence of initial LVN concentration and Fe 2+ concentration as catalyst on dissolved organic carbon (DOC) removal was thoroughly investigated. LVN was gradually mineralized by SPEF process, with faster DOC abatement at 0.50 mM Fe 2+, yielding 100% after 360 min at applied cathodic potential of −0.30 V|SHE. The high mineralization current efficiency (MCE) and low specific energy consumption (ECDOC ) revealed the extraordinary role of homogeneous hydroxyl radicals and natural UV light, which allowed the degradation of the antibiotic and its by-products with MCE values greater than 100%. Five cyclic by-products, N, N -diethylformamide and three short-chain linear carboxylic acids were detected by GC-MS and HPLC analyses. A parametric model to simulate the DOC decay versus electrolysis time was implemented for the SPEF pre-pilot flow plant, showing good agreement with experimental data. Highlights: Mineralization of levofloxacin solutions at pH 3.0 by SPEF in a flow plant. Total abatement of the antibiotic and its by-products upon action of OH and UV light. Mineralization current efficiencies >100% were found, attaining 1500% as maximum. 5 Cyclic derivatives and 3 aliphatic carboxylic acids, along with NO3 − and F − ions. SPEF plant modeled during the oxidation of levofloxacin by a parametric approach.